2013
DOI: 10.1016/j.pec.2012.12.015
|View full text |Cite
|
Sign up to set email alerts
|

‘They’ve just got symptoms without science’: Medical trainees’ acquisition of negative attitudes towards patients with medically unexplained symptoms

Abstract: Current medical training fails to equip doctors to engage with MUS and potentially fosters the development of unhelpful views of these patients. Informed teaching on diagnosis and management of MUS is necessary at a trainee level to limit the development of negative attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 37 publications
4
41
1
Order By: Relevance
“…10 A recent study exploring medical student attiudes also found a lack of formal training in medically unexplained symptoms, and senior role models to be influential in shaping students' attitudes and approach. 12 Patients' presenting symptoms varied according to specialty, although with some overlap in areas such as pain and fatigue, consistent with other studies. 13,14 Several doctors interviewed highlighted the importance of attempting to understand the patient's expectations, as in a recent review of the literature on effective communication with patients presenting with medically unexplained symptoms.…”
Section: Comparison With Existing Literaturesupporting
confidence: 88%
“…10 A recent study exploring medical student attiudes also found a lack of formal training in medically unexplained symptoms, and senior role models to be influential in shaping students' attitudes and approach. 12 Patients' presenting symptoms varied according to specialty, although with some overlap in areas such as pain and fatigue, consistent with other studies. 13,14 Several doctors interviewed highlighted the importance of attempting to understand the patient's expectations, as in a recent review of the literature on effective communication with patients presenting with medically unexplained symptoms.…”
Section: Comparison With Existing Literaturesupporting
confidence: 88%
“…The current study suggests that training and education for HPs may lack information about GID and the impact on daily life, relationships, and psychological health supporting research in medically unexplained symptoms . Therefore, more research needs to be conducted into this condition so that patients can be diagnosed and receive care sooner without encountering the struggle of “diagnosis by exclusion.” More research and wider dissemination of findings may also help raise awareness of GID in the general public. The benefits of this are 2‐fold, first helping to reduce stigma for those diagnosed with GID when out socially and second to help those who have not received a diagnosis recognize symptoms and receive appropriate treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Once the patient feels understood the GP can then go on to discuss the management of the condition [44]. CFS/ME therefore needs to be presented to students in a positive way, with clear and simple messages [45,46]. This could mean teaching students about these conditions first before they start to habitually use the biomedical model as a prototype for all conditions.…”
Section: Discussionmentioning
confidence: 99%